Sex Differences in Coronary Function Test Results in Patient With Angina and Nonobstructive Disease - Jansen, Tijn P. J.; Elias-Smale, Suzette E.; van den Oord, Stijn; Gehlmann, Helmut; Dimitiriu-Leen, Aukelien; Maas, Angela H. E. M.; Konst, Regina E.; van Royen, Niels; Damman, Peter (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Invasive coronary function testing (CFT) has become the recommended diagnostic tool to assess the various endotypes of coronary vasomotor dysfunction in patients with angina and no obstructive coronary artery disease (ANOCA), which has implications for therapy and prognosis. Although the expanding performance of CFT is leading to increased knowledge of coronary vasomotor dysfunction, little is known about sex-related differences in the results of comprehensive CFT. Methods: We conducted a prospective study of all consecutive patients with ANOCA that underwent clinically indicated CFT in a tertiary interventional from February 2019 to February 2021. CFT consisted of acetylcholine testing to diagnose epicardial or microvascular spasm, and adenosine testing to diagnose CMD. CMD was defined as an index of microvascular resistance (IMR) ≥ 25 and/or coronary flow reserve (CFR) < 2.0. Results: In total, 228 women and 41 men underwent CFT. No differences in traditional risk factors were seen, but women had a higher prevalence of migraine (45% vs. 14%, p=0.001). Men more often had a history of percutaneous coronary intervention (12% vs. 50%, p=0.001). We found no difference in clinical presentation. Coronary vasomotor dysfunction was present in 95% of men and 88% of women (p=0.21), but males show more often epicardial spasm and less microvascular spasm than women (64% vs. 42% and 29% vs. 40% respectively, p=0.027). Impaired CFR was more prevalent among females (3% vs 20%, p=0.001). IMR did not differ between the sexes. Conclusion: Men undergoing CFT show a comparable prevalence of coronary vascular dysfunction as women. However, men have a higher prevalence of epicardial spasm and a lower prevalence of microvascular spasm compared with women. An impaired CFR was more often present in women, with an equally impairment of IMR.